2015
DOI: 10.1128/aac.05179-14
|View full text |Cite
|
Sign up to set email alerts
|

Interplay among Membrane-Bound Lytic Transglycosylase D1, the CreBC Two-Component Regulatory System, the AmpNG-AmpD I -NagZ-AmpR Regulatory Circuit, and L1/L2 β-Lactamase Expression in Stenotrophomonas maltophilia

Abstract: e Lytic transglycosylases (LTs) are an important class of enzymes involved in peptidoglycan (PG) cleavage, with the concomitant formation of an intramolecular 1,6-anhydromuramoyl reaction product. There are six annotated LT genes in the Stenotrophomonas maltophilia genome, including genes for five membrane-bound LTs (mltA, mltB1, mltB2, mltD1, and mltD2) and a gene for soluble LT (slt). Six LTs of S. maltophilia KJ were systematically mutated, yielding the ⌬mltA, ⌬mltB1, ⌬mltB2, ⌬mltD1, ⌬mltD2, and ⌬slt mutant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…The CreBC TCS has been shown to be responsible for strain ΔdacB -mediated β-lactam resistance increases in P. aeruginosa ( 29 ), srtrain ΔdacB -mediated β-lactamase increases in A. hydrophilia ( 12 ), and strain Δ mltD1 -mediated L1/L2 expression increases in S. maltophilia ( 30 ). To elucidate whether the mutant ΔmrdA -mediated basal L1/L2 activity increase is related to the creBC TCS, the ΔcreBC allele was introduced into strain KJΔ mrdA , yielding the mutant KJΔ mrdA Δ BC , and its basal β-lactamase activity was determined.…”
Section: Resultsmentioning
confidence: 99%
“…The CreBC TCS has been shown to be responsible for strain ΔdacB -mediated β-lactam resistance increases in P. aeruginosa ( 29 ), srtrain ΔdacB -mediated β-lactamase increases in A. hydrophilia ( 12 ), and strain Δ mltD1 -mediated L1/L2 expression increases in S. maltophilia ( 30 ). To elucidate whether the mutant ΔmrdA -mediated basal L1/L2 activity increase is related to the creBC TCS, the ΔcreBC allele was introduced into strain KJΔ mrdA , yielding the mutant KJΔ mrdA Δ BC , and its basal β-lactamase activity was determined.…”
Section: Resultsmentioning
confidence: 99%
“…Individual deletion of MltB, MltF, Slt, and SltB1 mutant strains had no significant effect on either basal or cefoxitin-induced AmpC expression compared to the wild-type strain (Cavallari et al , 2013). Similarly, LT-gene knockouts in Stenotrophomonas maltophilia (including Slt, MltA, MltB1, MltB2, MltD1, and MltD2) explored the effects of loss of LT function in this species (Huang et al , 2015; Wu et al , 2016). Removal of one LT (MltD1) yielded high levels of uninduced β-lactamase activity, an undesirable phenotype.…”
Section: Lts As Targets For Antibiotic Developmentmentioning
confidence: 99%
“…aeruginosa . Nevertheless, we recently observed that the creD transcript has a 3.83 ± 0.33-fold increase when creBC is inactivated [ 14 ], which suggests that the regulatory circuit of creD expression in S . maltophilia is distinct and perhaps more complicated than that in E .…”
Section: Introductionmentioning
confidence: 99%